PERAN SOLAR ENERGY SAVITA SEBAGAI ENERGI ALTERNATIF DALAM PENYEDIAAN ENERGI LISTRIK PT TIRTA INVESTAMA MAMBAL - Gusti Putu Suryawan; I Gusti Ngurah Adia Atmika (Lembaga Penelitian dan Pengabdian Masyarakat (Institute for Research and Community Empowerment) Universitas Mahasaraswati Denpasar Bali, 2022)
Electric power is one type of energy that is needed in development. Therefore, with economic growth estimated at around 7%-10% per year until 2025, Indonesia's electricity consumption will increase rapidly. The amount of sunlight in tropical countries is very abundant, so that solar power generation is very suitable to be applied in Indonesia to save energy use. The potential of using solar power for electricity generation is quite promising as an alternative, because of the clean environment, unlimited resources and available throughout the country. In the development of renewable energy, the role of renewable energy in providing electrical energy at PT Tirta Investama Aqua Mambal is to be able to utilize solar thermal energy as a renewable energy power plant independently. The installed solar panels with a capacity of 600 Kwh are able to supply an effective average of 18-20% of the factory's operational needs or around 85,000 Kwh/month. The status of PT Tirta Investama Aqua Mambal is on-grade with PLN electricity. Thus, when there is no operation, then participate in exporting electrical energy to the PLN electricity network. With this system, it can reduce emissions by 898 Ton CO2/year, so it is necessary to develop independent Solar Energy in the future, not only concentrated in small units, but also in large units both in rural and urban areas. through the formulation of legal policies to support the development of Solar Energy.